2018
DOI: 10.2196/10034
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Cognitive Bias Modification Apps: Review of the Literature and of Commercially Available Apps

Abstract: BackgroundAutomatic processes, such as attentional biases or interpretative biases, have been purported to be responsible for several psychiatric disorders. Recent reviews have highlighted that cognitive biases may be modifiable. Advances in eHealth and mHealth have been harnessed for the delivery of cognitive bias modification. While several studies have evaluated mHealth-based bias modification intervention, no review, to our knowledge, has synthesized the evidence for it. In addition, no review has looked a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
0
42
0
1
Order By: Relevance
“…These tasks can be delivered via a variety of methods, but the most popular in the health domain are dot-probe, visual probe, and visual search tasks. All 3 tasks have been extensively used and reviewed in the literature [ 19 , 47 , 48 ]; however, historically, these tasks have been used in a laboratory setting, particularly in mental health interventions seeking to change anxiety and depression. This review revealed an expansion in the field, both in a real-world setting and in other health fields such as problem drinking, smoking, and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…These tasks can be delivered via a variety of methods, but the most popular in the health domain are dot-probe, visual probe, and visual search tasks. All 3 tasks have been extensively used and reviewed in the literature [ 19 , 47 , 48 ]; however, historically, these tasks have been used in a laboratory setting, particularly in mental health interventions seeking to change anxiety and depression. This review revealed an expansion in the field, both in a real-world setting and in other health fields such as problem drinking, smoking, and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions that gamified cognitive bias modification interventions target are like those targeted by conventional mobile-based cognitive bias modification interventions. The review by Zhang et al [ 23 ] evaluated the published literature and reported that out of 8 identified studies, at least 4 studies used a mobile intervention to target anxiety-related disorders (anxiety and social anxiety disorders). In their review of meta-analyses, Jones et al [ 10 ] included 5 meta-analyses that examined anxiety-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…User perspectives of what makes an app engaging and which strategies result in short and longer term engagement are important to consider in the design of gamified cognitive bias modification interventions. While only 4 studies were identified for this review, Zhang et al [ 23 ] found that there were 17 commercial cognitive bias modification apps in the app stores. It might be helpful to analyze the gamification features in commercial cognitive bias modification apps and see if certain gamification features are associated with higher rates of downloads, a surrogate measure of acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…The perspectives of patients and public is important in the design of gamified cognitive bias modification intervention informing us about what they feel might help make the application more engaging and what strategies, when applied, would result in both short and longer-term engagement. While only four studies are identified for this review, Zhang et al (2018) have in their prior review highlighted that there are seventeen cognitive bias modification commercial applications on the application stores. It might be helpful to analyse the gamification features in commercial cognitive bias modification applications and see if certain gamification features are associated with higher rates of downloads, a surrogate measure of acceptability.…”
Section: Discussionmentioning
confidence: 99%